RISK FACTORS FOR EARLY PRETERM LABOUR AND THEIR DYNAMICS IN WOMEN OF THE SLAVIC POPULATION - Ремнева, Ольга Васильевна; Колядо, Ольга Викторовна; Ховалыг, Нелля Михайловна (Mother and Baby in Kuzbass, 2020)
The aim of the research. To determine the risk factors for spontaneous early preterm birth and their dynamics for the period 2005-2019 in women of the Slavic population. Materials and methods. Women of the Slavic population with a history of spontaneous early preterm birth for the period 2005-2006 were included in a retrospective simultaneous (transverse) study. The study was performed in the Perinatal Centre of the Altai Region, Barnaul – the clinical base of the Department of Obstetrics and Gynecology of the Altai State Medical University. In 2018-2019 a similar clinical and statistical analysis of cases of preterm birth was carried out on the base of the Altai State Clinical Perinatal Center. The main group I consisted of 186 women who were delivered at 28-33.6 weeks of gestation in 2005-2006, the main group II consisted of 67 women, delivered at the same gestational age in 2018-2019. The control group was represented by 107 women with spontaneous term delivery. Based on an analytical case-control study, risk factors for early preterm birth were identified. Results. It was found that socio-demographic risk factors for spontaneous early preterm birth are: young (OR 7.3; 95% CI 0.93-57.0) and late reproductive age (OR 2.3; 95% CI 1.24-4 , 55), hard physical work (OR 2.1; 95% CI 1.15-4.00), extramarital birth (OR 5.9; 95% CI 1.36-26.17). Medical and biological risk factors are chronic inflammatory diseases of the otolaryngologic sphere (OR 4.9; 95% CI 2.01-11.98), urinary tract (OR 2.0; 95% CI 1.04-4.01), socially significant infections (OR 3.0; 95% CI 1.11-8.17), smoking (OR 2.2; 95% CI 1.09-4.59), history of artificial abortions (OR 5.7 95 % CI 2.93-11.14), preterm labour (OR 5.6; 95% CI 1.27-24.73) and miscarriage (OR 3.1; 95% CI 1.82-7.77). The study of dynamic changes in the risk factors for the period 2005-2019 demonstrated an increase in single women of late reproductive age with a personal history of preterm labor. Conclusion. Analysis and accounting of risk factors for spontaneous early preterm birth allows to perform differentiated preventive measures before and during pregnancy.